2021
DOI: 10.1093/aob/mcab083
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and gene expression analysis of flowering time regulation by light quality in lentil

Abstract: Background and Aims Flowering time is important due to its roles in adaptation to different environments and subsequent formation of crop yield. Changes in light quality affect a range of developmental processes including flowering time, however little is known about light quality induced flowering time control in lentil. This study aims to investigate the genetic basis for differences in flowering response to light quality in lentil. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 83 publications
1
14
0
Order By: Relevance
“…In a recent study parallel to this one, interspecific genetic analysis of flowering time differences between L. culinaris and its putative wild ancestor L. orientalis also revealed a QTL co-locating with qDTF6a , and identified FTa1 as the only differentially regulated candidate gene within the QTL interval ( Yuan et al , 2021 ). Interestingly, in this case, FTa1 expression was higher, and flowering was earlier, in the wild parent relative to the domesticated parent cv.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In a recent study parallel to this one, interspecific genetic analysis of flowering time differences between L. culinaris and its putative wild ancestor L. orientalis also revealed a QTL co-locating with qDTF6a , and identified FTa1 as the only differentially regulated candidate gene within the QTL interval ( Yuan et al , 2021 ). Interestingly, in this case, FTa1 expression was higher, and flowering was earlier, in the wild parent relative to the domesticated parent cv.…”
Section: Discussionmentioning
confidence: 81%
“…The closely related species pea has six FT genes ( Hecht et al , 2011 ; Ortega et al , 2019 ), and an analysis of the recently released lentil genome sequence has confirmed that the same is also true in lentil ( Yuan et al , 2021 ; Supplementary Fig. S5 ).…”
Section: Resultsmentioning
confidence: 89%
“…The closely related species pea has six FT genes (Hecht et al 2011; Ortega et al 2019), and an analysis of recently released lentil genome sequence has confirmed that the same is also true in lentil (Yuan et al 2021, Supp Figure 5 ). The results in Figure 5B show that in leaf tissue of three-weeks old plants grown under SD conditions, both FTa1 and FTa2 genes were expressed at a significantly higher level in NILs carrying the dtf6a allele compared to equivalent plants with the DTF6a allele.…”
Section: Resultsmentioning
confidence: 88%
“…By changing this ratio in controlled growth chambers, we can simulate the effect of shading on plants while controlling for confounding effects such as competition for other resources. Results from our earlier lentil study ( Yuan et al, 2021 ) suggested potential roles for genes within the florigen gene family, several MADS-box transcription factors, and bHLH transcription factors, in regulating flowering time under such conditions in lentils. In this study, we used a holistic approach to examine the gene expression changes under different light qualities, as well as gene functionalities between the cultivated lentil and its wild relative, L. orientalis , to help better understand SAS in lentils.…”
Section: Discussionmentioning
confidence: 99%